2017
DOI: 10.1371/journal.pone.0186576
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of extended spectrum β-lactamase producing Escherichia coli from clinical, recreational water and wastewater samples associated in time and location

Abstract: Extended spectrum β-lactamase producing Escherichia coli (ESBL-EC) are excreted via effluents and sewage into the environment where they can re-contaminate humans and animals. The aim of this observational study was to detect and quantify ESBL-EC in recreational water and wastewater, and perform a genetic and phenotypic comparative analysis of the environmental strains with geographically associated human urinary ESBL-EC. Recreational fresh-and saltwater samples from four different beaches and wastewater sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 48 publications
10
65
0
Order By: Relevance
“…This sub-clone has spread as a pandemic among humans, often identified as the pathogen in severe bloodstream infections [ 33 ]. Secondly, ST617, ST38 and ST10, found in one, two and seven gulls respectively, are also sequence types with clinical importance in human medicine [ 34 37 ]. A recent study also described high relatedness of clinical isolates of ST38 from UK and one isolate of ST38 isolated from a Mongolian wild bird [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This sub-clone has spread as a pandemic among humans, often identified as the pathogen in severe bloodstream infections [ 33 ]. Secondly, ST617, ST38 and ST10, found in one, two and seven gulls respectively, are also sequence types with clinical importance in human medicine [ 34 37 ]. A recent study also described high relatedness of clinical isolates of ST38 from UK and one isolate of ST38 isolated from a Mongolian wild bird [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the isolates from gulls and humans showed high similarities to those originating from Swedish surface waters, suggesting WWTPs as one possible source. Comparable a recent Norwegian study described that ST131, ST10 and ST38 carrying the genes bla CTX-M-1 , bla CTX-M-14 and bla CTX-M-15 were frequently identified from surface waters, wastewaters and human UTIs [ 37 ]. The same gene and MLST combinations were also frequent in Swedish gulls, humans and surface waters ( Table 1 , Fig 1 , Fig 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The whole genome sequencing of C. difficile strains, which are a commensal organism and a pathogen in both human and animal [39], showed that C. difficile isolates with identical (no SNP differences) and almost identical (less than two SNP differences) are detected in both farmers and pigs in the Netherlands [34]. Many β-lactam-resistant E. coli strains identified in human samples were also detected in animals [29,31,[35][36][37][38] and environment [35,40,41]. These results indicate the complex transmission of β-lactam-resistant E. coli strains among human, animal, and environment.…”
Section: Observational Evidences For the Transmission Of Antibiotic Rmentioning
confidence: 99%
“…Enterobacteriaceae [59] Quinolone and fluoroquinolone Salmonella enterica [16] Escherichia coli [32] Sulfamethoxazole Salmonella enterica [16] Tetracycline Clostridium difficile [34] Multidrug Escherichia coli [33] Identification of the same genetic mobile element carrying the antibiotic resistance gene β-Lactam Escherichia coli [29,31,36,[60][61][62] Salmonella enterica [18,27,63] Colistin Escherichia coli [44][45][46][47][48][49][50][51] Salmonella enterica [64] Tetracycline Staphylococcus aureus [65] Environment and human Identification of the same antimicrobial-resistant strain β-Lactam Escherichia coli [35,41,66] Enterobacteriaceae [59] Multidrug Escherichia coli [40] Identification of the same genetic mobile element carrying the antibiotic resistance gene β-Lactam Enterobacteriaceae [67] Colistin Escherichia coli [53]…”
Section: Species Referencesmentioning
confidence: 99%
“…have been reported in healthcare institutions in Norway [ 4 6 ]. Yet another concern is that ESC-resistance often occurs along with co-resistance to important non-beta-lactam antibiotic classes [ 7 ], significantly limiting treatment options for these patients.…”
Section: Introductionmentioning
confidence: 99%